2013
DOI: 10.1007/s11046-013-9668-6
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and molecular identification of Sporothrix isolates of clinical origin in Northeast China

Abstract: Sporotrichosis is the most common deep mycosis in Northeast China which is an area of high epidemicity due to contact with reeds or cornstalks. In this study, we have characterized a total of 74 clinical isolates from fixed cutaneous, lymphocutaneous and disseminated clinical forms and from Heilongjiang, Jilin, and Liaoning provinces, respectively. All isolates (previously as Sporothrix schenckii) were identified as Sporothrix globosa according to their phenotypic characteristics and calmodulin gene sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 17 publications
7
47
0
Order By: Relevance
“…25,26 Our patient was engaged in rural activities that put him at risk of traumatic infection during handling of contaminated materials. 11,25,27 The strain of S. globosa isolated in this study had phenotypic similarities to clinical S. globosa strains reported previously, 11,12,28 although it was able to grow at 37°C, in contrast with the findings of Marimon and others. 5 Although S. globosa is thought to have several clinical manifestations, such as fixed cutaneous, lymphocutaneous, and disseminated cutaneous manifestations, 2,11 clinical reports involving S. globosa mostly have few clinical details.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…25,26 Our patient was engaged in rural activities that put him at risk of traumatic infection during handling of contaminated materials. 11,25,27 The strain of S. globosa isolated in this study had phenotypic similarities to clinical S. globosa strains reported previously, 11,12,28 although it was able to grow at 37°C, in contrast with the findings of Marimon and others. 5 Although S. globosa is thought to have several clinical manifestations, such as fixed cutaneous, lymphocutaneous, and disseminated cutaneous manifestations, 2,11 clinical reports involving S. globosa mostly have few clinical details.…”
Section: Discussionsupporting
confidence: 49%
“…11,25,27 The strain of S. globosa isolated in this study had phenotypic similarities to clinical S. globosa strains reported previously, 11,12,28 although it was able to grow at 37°C, in contrast with the findings of Marimon and others. 5 Although S. globosa is thought to have several clinical manifestations, such as fixed cutaneous, lymphocutaneous, and disseminated cutaneous manifestations, 2,11 clinical reports involving S. globosa mostly have few clinical details. 9,17 Sporothrix globosa species are considered to be low virulent or even avirulent by some researchers, 13,14 and the large sapronoses occurring in China reflects localized manifestations of the disease.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The incidence of sporotrichosis is increasing in China, particularly in the northeastern region of the country (Zhang and Lin, 2008). Sporothrix globosa was identified as the causal agent of sporotrichosis in many of these cases (Tan et al, 2013;Yu et al, 2013;Liu et al, 2014;Zhou et al, 2014). Four species of the Sporothrix complex have been reported as causal agents of sporotrichosis: S. brasiliensis, S. globosa, S. schenckii s.…”
Section: Introductionmentioning
confidence: 99%
“…Different clinical forms of sporotrichosis are related to the condition of the host, route of infection, and virulence of the pathogen, and virulence may be associated with different Sporothrix species (Arrillaga-Moncrieff et al, 2009;Fernandes et al, 2013). Previous studies have shown that S. globosa is the causal agent of sporotrichosis in China (Tan et al, 2013;Yu et al, 2013;Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%